-17+15=-2(x+9)

Simple and best practice solution for -17+15=-2(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17+15=-2(x+9) equation:



-17+15=-2(x+9)
We move all terms to the left:
-17+15-(-2(x+9))=0
We add all the numbers together, and all the variables
-(-2(x+9))-2=0
We calculate terms in parentheses: -(-2(x+9)), so:
-2(x+9)
We multiply parentheses
-2x-18
Back to the equation:
-(-2x-18)
We get rid of parentheses
2x+18-2=0
We add all the numbers together, and all the variables
2x+16=0
We move all terms containing x to the left, all other terms to the right
2x=-16
x=-16/2
x=-8

See similar equations:

| 2(w+9)=4w+14 | | 3/2(4x–1)–3x=54–(x+2) | | 8x+7+2x+8=125 | | n+4n=230 | | 11x-2+x-6=4(x+3)+8(x+12) | | 3x^2+76+88-2x^2=180 | | -10(n+5)=40 | | 1920=16t^2 | | 6-2y=3y+1 | | --5x16=9x+x-1 | | 7(x-9)+2=-61 | | -2x-3=3x-4-7x | | Y=6x^2+17x+12 | | d=5*19 | | 13y+19=6(9-y)+14 | | 200m-100m+475000=50500-150m | | 5*(x-4)=7x-83 | | 10m−8=8m+6 | | 5x(x-4)=7x-83 | | 22x-5+20x+7=180 | | 7(x-9)=2=-61 | | -3(9z+6)=-29-8z | | x=(-1) | | -23x2+92=0 | | 5(x-4)=7x-83 | | -72=-6-3(-5x+9) | | 3(x-2)^2+54=0 | | 3(3-7k)=-7(-1+3k)-1 | | f(-12)=11 | | -8.01+7.6c=18.39+14.2c | | 12b+9+5b=10(4b+9)-4(b+6) | | 18-1x=30-2x |

Equations solver categories